Impact of the Health Resources and Services Administration's state oral health workforce grant program on dental workforce density and access to oral health care. (August 2019) - Chou, Chiu-Fang; Vallin, Thomas; Rogers, Shane; Streeter, Robin A.; Worede, Isaac; Washko, Michelle M.; Zangaro, George A.; Ungard, Jesse
Highlights: Multi-year HRSA's State Oral Health Workforce Grant Program is associated with higher workforce density and thus, greater access to oral health care, especially in the Midwest and West. These findings may help to guide next steps for directing and evaluating HRSA's State Oral Health Workforce Grant activities, as well as contribute to planning and policy decisions about whether and how to scale state level workforce development programs to have the greatest impact on improving oral health. Abstract: Background: The Health Resources and Services Administration's Grants to States to Support Oral Health Workforce Activities, otherwise known as the State Oral Health Workforce Program (SOHWP), help states develop and implement innovations that address the workforce needs of dental Health Professional Shortage Areas in a manner appropriate to the states' individual needs. Aim: This cross-sectional study explores the broad impact of the SOHWP by comparing measures of dental workforce density and access to oral health care in states with multiple years of funding versus states with few or no years of funding. Methods: We used data for 2006–2016 SOHWP awardees together with data from the 2016–2017 Area Health Resources Files and the 2016 Behavioral Risk Factor Surveillance System to compare numbers of dentists per 100, 000 population and age-adjusted prevalence of annual dental visits among adults for long-term SOHWP-funded states versus states with few or no years of funding. Results: Multi-year SOHWP funding is associated with higher workforce density and greater access to oral health care, especially in the Midwest and West. Conclusion: Allowing states funding utilization flexibility may result in improved outcomes. This finding can help inform planning and policy about whether and how to scale future training and workforce programs to achieve greater impact.